Phenolic content and antioxidant activity of crude and fractionated extracts of Pereskia bleo (Kunth) DC. (Cactaceae) - Sim, K.S.; Sri Nurestri, A.M.; Norhanom, A.W. (2010)
The total phenolic content of the extracts of Pereskia bleo were assessed by the Folin-Ciocalteau’s method while the antioxidant activities were determined by three different assays, namely scavenging activity on 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals, reducing power assay and ß-carotene method. In the present study, the ethyl acetate extract exhibited the highest total phenolic content (40.12 mg of GAEs/g of extract) and showed the strongest antioxidant activity in the ß-carotene bleaching assay significantly. Whilst, the hexane extract showed significantly the highest antioxidant activity when determined by scavenging effect on DPPH radicals (EC50 210 μg/ml) and the reducing power assay.